Use of Technology in Tax Administrations 1 : Developing an Information Technology Strategic Plan (ITSP) - Cotton, Margaret (Technical Notes and Manuals; Technical Notes and Manuals, 2017)
This technical note is the first of three addressing information technology (IT) themes and issues relevant to tax administrations. This note focuses on the use of technology in tax administrations and how to develop an information technology strategic plan (ITSP). It is intended for tax administrations that are largely manual or have outdated legacy IT systems. The second note addresses how to select an IT system for core tax administrations functions. And the third note covers implementation of a commercial-off-the-shelf (COTS) system. These technical notes are primarily for use by tax administrations that have no technology to manage their core tax processes, or their technology is limited and outdated. These notes focus on core tax functions and do not address other business systems (e.g., payroll, finance, document, and asset management systems).